Biomechanical Investigation of the Efficacy of Conventional Bicycle Helmets at Preventing Facial Injury - Ghaidaa A. Khalid (Journal of Techniques)
Many studies indicate that wearing a bicycle helmet significantly reduces the risk of accident-related head injuries. Less is reported, however, about bicycle helmet use, about preventing facial injury. Epidemiological studies typically report incidences of 'head injury,' though rarely categorize head, brain, and facial injuries separately. Studies that do focus on facial injury suggest that helmets do not provide adequate protection. A 3D biofidelic child head form and two conventional bicycle helmets (that is,” open face") were created in MSC ADAMS™ computer modelling and simulation software. Peak force and linear accelerations were measured for a series of head form impact simulations corresponding to an established testing standard and a newly proposed series of tests derived from modified motorcycle standards, incorporating injury thresholds from the facial bone impact tolerance literature. Almost all impact simulations exceeded the threshold for fracture, soft tissue, and dental trauma. An observational study was conducted using MSC ADAMS™ to assess a helmeted headform's face exposure during impact simulations. Helmets failed to reduce face impact exposure, during all simulations, except for perpendicular cheek impacts. International test standards, therefore, require urgent revision to ensure that face protection is included.